PERFOMANCE TEST OF MRI MACHINES IN THE PROVINCE OF BALI - Gusti Bagus Yudhi Jaya Putra Atmaja; Gatot Murti Wibowo; Bagus Abimanyu (Poltekkes Kemenkes Semarang, 2018)
Backgroud: The research of performance test of MRI machines were done by doing performance test of nine different parameters in three hospitals in the province of Bali, where in two of these three hospitals are having troubled MRI machines which directly affected the image quality and therefore this research is also aimed to find out the performance of MRI machines in some hospitals in the province of Bali and intended as a baseline data if there will another test.Methods: This research is a quantitative study with survey approach. The tools and materials for this research were three MRI machines, which was consisted of two 1,5 Tesla machines and a 0,3 Tesla machine, phantom ACR, and MRI head coil. The data were collected by doing nine MRI performance testing procedures with ACR (2015) as a guideline and then the data were analyzed using international standards issued by ACR (2015).Results: Visual checklist test result of all the hospitals get 12 pass every day from the first day to the twentieth day. SNR test in Badung Regional General Hospital obtain measurement results of 268.17 and in The Board Of Tabanan General Hospital at 15.78 and at Sanglah Central General Hospital of 2.4. To test the artifact analysis only in The Board Of Tabanan General Hospital only found one type of artifact is the artifact geometric distortion. In testing the high contrast resolution in Sanglah Central General Hospital and Badung Regional General Hospital get the same result, namely insert a separate resolution of up to a third group, and the The Board Of Tabanan General Hospital insert a separate resolution to the second group. The test results in low contrast resolution Sanglah Central General Hospital and Badung Regional General Hospital get the same result, namely that there are 10 spokes are visible, then the The Board Of Tabanan General Hospital number of spokes that appear are 9 spokes. In testing the slice thickness accuracy in Sanglah Central General Hospital get the standard deviation of measurement of 5.12mm and in Badung Regional General Hospital get the standard deviation and the measurement of 0.64mm in The Board Of Tabanan General Hospital get the standard deviation of measurement of 0.48mm. Results of the geometric accuracy test in The Board Of Tabanan General Hospital has a difference measurement of 4.2mm X axis, Y-axis of 1.3mm, and has no difference in the Z-axis, in Badung Regional General Hospital has a difference of X-axis measurement of -3.1mm, have no difference in the Y axis the Z axis of 2mm, in Sanglah Central General Hospital has a difference measurement of 1.36mm X axis, Y-axis and Z-axis of 0.39mm for -3.53mm. The test results slice position accuracy in Sanglah Central General Hospital get the standard deviation measurements for -1.33mm, in The Board Of Tabanan General Hospital of 0.85mm, and in Badung Regional General Hospital of -0.3mm. For the test setup and table position accuracy throughout the hospital to get the same measurement is 5mm.Conclusion: Out of nine parameters in the test : only four parameters, which were high contrast resolution test, low contrast resolution test, slice position accuracy test, and setup and table position accuracy test, that met the international standards in all hospitals, whereas all the hospital didn’t meet the international standards in geometric accuracy test. There were two hospitals that didn’t meet the international standards in signal to noise ratio test, while one hospital didn’t meet the standards in artifact analysis test and slice thickness accuracy test.